Sustaining Soil Productivity by Integrated Plant Nutrient Management in Wheat Based Cropping System Under Rainfed Conditions: Soil Productivity through IPNM for Wheat Crop - Dilshad, Mohiuddin; Lone, Mohammad Iqbal; Jilani, Ghulam; Malik, Muhammad Azim; Yousaf, Muhammad; Khalid, Rizwan; Shamim, Fakhra (Biological Sciences - PJSIR, 2011)